Pengendalian Kualitas terhadap Kerusakan MC Tembakau pada Proses Redrying dengan Pendekatan metode Six Sigma - Muhammad, Erick; Ardana Putri, Farahdiansari (Jurnal Teknologi dan Manajemen Sistem Industri, 2023)
This research was conducted at the KAREB Cooperative, a company that provides tobacco redrying services. The cooperative processes tobacco from various consumers in the thresher unit, where production can last up to 15 hours. Such extended operations increase the risk of machine malfunctions. To address this, the company implements quality control measures based on predefined standards to minimize defective products and ensure that outputs meet quality requirements. These measures also aim to prevent defective items from reaching consumers. One of the quality control approaches applied is the Six Sigma method, which focuses on defect reduction through a structured process of defining, measuring, analyzing, improving, and controlling production quality. The methodology involves detailed data breakdown, including data presentation, analysis, and interpretation. Data were collected through interviews and discussions with the quality control team at the KAREB Cooperative, providing insights into the practical application of Six Sigma in tobacco redrying operations.